Empowering communities through the sustainable transformation of used cooking oil waste into aromatherapy candles: A holistic approach to waste management - Nurul Shofiah; Husna Malikatus Siswanto; Novita Ramadhanfi Maulani; Suwito Setyo Wicaksono (Journal of Community Service and Empowerment, 2025)
Used cooking oil from household frying is often discarded improperly, leading to environmental pollution. One sustainable solution is repurposing it into aromatherapy candles, reducing waste while creating economic opportunities. To address this issue, KKM 210 UIN Malang conducted a community service initiative titled "Optimizing the Transformation of Used Cooking Oil Waste into Aromatherapy Candles: A Sustainable Waste Management Approach" in Petungsewu Village, in collaboration with PKK members. This program aimed to raise awareness of the dangers of reusing used cooking oil, reduce improper disposal, and introduce innovative business ideas. The socialization included brochure distribution, material presentations, hands-on training, interactive Q&A sessions, and entrepreneurship guidance. A pre- and post-assessment was conducted to measure knowledge retention and skill acquisition. Results showed a significant increase in participant understanding, with knowledge of candle-making rising by 65% and 85% of participants gaining confidence in independent production. Additionally, 75% of participants expressed interest in developing a home-based business, demonstrating the initiative’s potential for local economic development. These findings highlight the importance of transforming used cooking oil into value-added products as both an eco-friendly waste management solution and a means of empowering local communities. The initiative serves as a model for sustainable development, showcasing how practical innovations can address both environmental and economic challenges. Future programs should focus on expanding training, facilitating market access, and supporting small business growth to ensure long-term impact and scalability.